Effect of Co-culturing both placenta-derived mesenchymal stem cells and their condition medium in the cancer cell (HepG2) migration, damage through apoptosis and cell cycle arrest - Opo, F.A. Dain Md; Moulay, Mohammed; Alrefaei, Ghadeer I.; Alsubhi, Nouf H.; Alkarim, Saleh; Rahman, Mohammed M. (Saudi journal of biological sciences, 2023)
Human placental-derived mesenchymal stem cells (hPMSCs) are a promising candidate to inhibit the proliferation of hepatocellular carcinoma (HCC) cell lines such as HepG2. The effects of hPMSCs and their conditioned media on HepG2 are, however, still a mystery. As a result, the goal of this study was to look into the effects of hPMSCs and their conditioned media on HepG2 and figure out what was going on. Fluorescence-activated cell sorting and the MTT test were used to determine the percentage of cells that died (early apoptosis, late apoptosis). The DIO and DID colors were used to detect cell fusion and cell death in both cells. HepG2 cells were co-treated with hPMSCs or hPMSCs-conditioned medium (hPMSCs-CM) to reduce growth and promote apoptosis. Morphological changes were also seen in the 30 percent, 50 percent, and 60 percent cases. The secretion of cytokine was determined by the ELISA. Flow cytometry, caspase 9 immunofluorescence, qPCR (detection of Bax, Bcl-2, and β-catenin genes), western blot, and immunophenotyping revealed that treatment with hPMSCs or hPMSCs-CM caused HepG2 cell death through apoptosis (detection of caspase 9, caspase 3 protein). HepG2 cell cycle arrest could be induced by hPMSCs and hPMSCs-CM. Following treatment with hPMSCs or hPMSCs-CM, HepG2 cell development was stopped in the G0/G1 phase. These treatments also inhibited HepG2 cells from migrating, with the greatest effect when the highest ratio/concentration of hPMSCs (70%) and hPMSCs-CM were used (90%). Our findings indicated that hPMSCs and hPMSCs-CM could be promising treatment options for liver cancer. To elucidate the proper effect, more research on liver cancer-induced rat/mice is needed.